Impact of COVID-19 early in the pandemic on the mental health and wellbeing of adolescents in Australia and Cambodia: a cross-national comparison using a quantitative descriptive and comparative approach - Van Dyke, Nina; Keo, Sam Oeun; de Courten, Maximilian P. (Frontiers in Public Health, 2024)
The impact of COVID-19 on the mental health and wellbeing of adolescents is a major concern. Most research has been conducted only in more economically developed countries. Using data from two similar surveys administered during July–September, 2020 in Australia (a high-income country) and Cambodia (a low-middle income country), this paper examined the impact early in the pandemic on the mental health and wellbeing of adolescents in the two countries. We found that COVID-19 had mostly negative impacts on participants' mental health; threats to personal safety; education; support for schooling; basic necessities such as food, income, employment, and housing; and responsibilities at home. This finding suggests that even short-term disasters may have negative repercussions, and regardless of differences in wealth, culture, and government response. We found that threats to personal safety appeared to be more prevalent in Cambodia than in Australia, the impact on mental health of the Cambodian participants may have been greater than reported, and that, in both countries, support for online or distance schooling during periods of lockdown was wanting, particularly at the state and school levels. This study will contribute to our understanding of the impact of major disruptive global events on young people in both more economically developed and developing countries.